Xenogeneic Sertoli cells modulate immune response in an evolutionary distant mouse model through the production of interleukin-10 and PD-1 ligands expression - Vegrichtova, Marketa; Hajkova, Michaela; Porubska, Bianka; Vasek, Daniel; Krylov, Vladimir; Tlapakova, Tereza; Krulova, Magdalena (Xenotransplantation, 2022)
BACKGROUND: Immunomodulatory mechanisms of Sertoli cells (SCs) during phylogeny have not been described previously. This study attempted to reveal mechanisms of SC immune modulation in an evolutionary distant host. METHODS: The interaction of the SC cell line derived from Xenopus tropicalis (XtSC) with murine immune cells was studied in vivo and in vitro. The changes in the cytokine production, the intracellular and surface molecules expression on murine immune cells were evaluated after co-culturing with XtSCs. Migration of XtSCs in mouse recipients after intravenous application and subsequent changes in spleen and the testicular immune environment were determined by flow cytometry. RESULTS: The in vitro co-culture model was established, allowing the study of XtSCs interaction with murine immune cells. Intracellular staining of interleukin (IL-)10 revealed a significant increase in its expression in macrophages and B cells co-cultured with XtSCs, compared to both unstimulated cells and xenogeneic control. On the contrary, a significant decrease in Th lymphocytes expressing interferon-gamma was observed. The expression of both PD-1 ligands (PD-L1 and PD-L2) was upregulated on the macrophage surfaces after co-culture with XtSCs, but not with the controls. XtSCs migrated specifically to testes when administered intravenously and modulated systemic and local testicular microenvironment; this was detected by the expression of molecules associated with suppressive phenotype by CD45+ cells in both spleen and testes. CONCLUSION: We have demonstrated for the first time that SCs can migrate and modulate immune response in a phylogenetically distant host. It was further observed that SCs induce expression of molecules associated with immunosuppression, such as IL-10 and PD-1 ligands.
Keywords: Disease Models, Animal; Immunity; myši; Animals; Ligands; mužské pohlaví; Sertoli cells; xenotransplantation; interleukin-10; ligandy; immunomodulation; modely nemocí na zvířatech; B7-H1 Antigen; Programmed Cell Death 1 Receptor; Mice; antigeny CD274; zvířata; Sertoli Cells; antigeny CD279; Sertoliho buňky; Interleukin-10; imunita; transplantace heterologní; Male; Transplantation, Heterologous